Impacts of urban forests on offsetting carbon emissions from industrial energy use in Hangzhou, China (2010)
This study quantified carbon storage and sequestration by urban forests and carbon emissions from energy consumption by several industrial sources in Hangzhou, China. Carbon (C) storage and sequestration were quantified using urban forest inventory data and by applying volume-derived biomass equations and other models relating net primary productivity (NPP) and mean annual biomass increments. Industrial energy use C emissions were estimated by accounting for fossil fuel use and assigning C emission factors. Total C storage by Hangzhou's urban forests was estimated at 11.74 Tg C, and C storage per hectare was 30.25 t C. Carbon sequestration by urban forests was 1,328, 166.55 t C/year, and C sequestration per ha was 1.66 t C/ha/year. Carbon emissions from industrial energy use in Hangzhou were 7 Tg C/year. Urban forests, through sequestration, annually offset 18.57% of the amount of carbon emitted by industrial enterprises, and store an amount of C equivalent to 1.75 times the amount of annual C emitted by industrial energy uses within the city. Management practices for improving Hangzhou's urban forests function of offsetting C emissions from energy consumption are explored. These results can be used to evaluate the urban forests' role in reducing atmospheric carbon dioxide.